CURRENT STATE OF THE PROBLEM OF INCREASE QUALIFICATIONS OF TEACHERS PHYSICAL EDUCATION - Andrivnov, V.Ye.; Marchyk, V.I.; Andrianov, T.V. (Pedagogy of Higher and Secondary Education, 2022)
The article is devoted to the modern problems of increasing qualification of physical training teacher.